A More Homogeneous Phenotype in Parkinson's Disease Related to R1441G Mutation in the LRRK2 Gene - Vinagre-Aragón, Ana; Campo-Caballero, David; Mondragón-Rezola, Elisabet; Pardina-Vilella, Lara; Hernandez Eguiazu, Haizea; Gorostidi, Ana; Croitoru, Ioana; Bergareche, Alberto; Ruiz-Martinez, Javier (Frontiers in Neurology, 2021)
Parkinson’s disease (PD) is characterized by a great clinical heterogeneity. Nevertheless, the  biological drivers of this heterogeneity have not been completely elucidated and are likely to be complex, arising from interactions between genetic, epigenetic and environmental factors. Despite  this heterogeneity, the clinical patterns of monogenic forms of PD have usually maintained a good  clinical correlation with each mutation once a sufficient number of patients have been studied.  Mutations in LRRK2 are the most commonly known genetic cause of autosomal dominant PD known  to date. Furthermore, recent genome-wide association studies have revealed variations in LRRK2 as  significant risk factors also for the development of sporadic PD. The LRRK2-R1441 mutation is  especially frequent in population of Basque ascent based on a possible founder effect, being  responsible for almost 50% of cases of familial PD in our region, with a high penetrance. Curiously,  Lewy bodies, considered the neuropathological hallmark of PD, are absent in a significant subset of  LRRK2-PD cases (including the neuropathological study of three PD LRRK2-R1441). Indeed, these  cases appear to be associated with a less aggressive primarily pure motor phenotype. The aim of our  research is to examine the clinical phenotype of R1441G-PD patients, more homogeneous when we  compare it with idiopathic PD patients or with patients carrying other LRRK2 mutations, and reflect  on the value of the observed correlation in the genetic forms of PD. The clinical heterogeneity of PD  leads us to think that there may be as many different diseases as the number of people affected.  Undoubtedly, genetics constitutes a relevant key player, as it may significantly influence the  phenotype, with differences according to the mutation within in the same gene, and not only in  familial PD but also in sporadic forms. Thus, extending our knowledge regarding genetic forms of  PD implies an expansion of knowledge regarding sporadic forms and this may be relevant due to the  future therapeutic implications of all forms of PD.